Pengaruh Environmental, Social, Governance (ESG) Disclosure dan Struktur Modal Terhadap Tingkat Profitabilitas Perusahaan: Studi Kasus Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Nabila Atiqa Ma’ruf; Suyatmin Waskito Adi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of Environmental Disclosure, Social Disclosure, Governance Disclosure, and Capital Structure on the profitability of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of 2021-2023. Using a quantitative approach, secondary data obtained from financial and sustainability reports of companies were analyzed through multiple linear regression. The results indicate that Environmental Disclosure and Social Disclosure significantly affect profitability, with significance values of 0.022 and 0.004, respectively. However, Governance Disclosure does not have a significant effect on profitability, with a significance value of 0.809, while Capital Structure has a significant effect with a significance value of 0.000. This study has limitations in the sample, which only includes manufacturing companies on the IDX, as well as a limited observation period from 2021 to 2023. Therefore, it is recommended that future research expands the sample and observation period and adds other variables that may influence company profitability.